2021
DOI: 10.21203/rs.3.rs-244755/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid sequence evolution driven by transposable elements at a virulence locus in a fungal wheat pathogen

Abstract: Background: Plant pathogens cause substantial crop losses in agriculture production and threaten food security. Plants evolved the ability to recognize virulence factors and pathogens have repeatedly escaped recognition due rapid evolutionary change at pathogen virulence loci (i.e. effector genes). The presence of transposable elements (TEs) in close physical proximity of effector genes can have important consequences for gene regulation and sequence evolution. Species-wide investigations of effector gene loci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…We analysed pathogenicity profiles for a subset of 120 isolates out of the total number of isolates analysed in this study. The pathogenicity assay dataset was generated to perform genome-wide association studies [45]. In summary, seedlings of the cultivar Claro were grown under controlled conditions as follows: 16/8 h day/night periods at 18 °C throughout the experiment.…”
Section: Culture Preparation and Seedling Infection Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…We analysed pathogenicity profiles for a subset of 120 isolates out of the total number of isolates analysed in this study. The pathogenicity assay dataset was generated to perform genome-wide association studies [45]. In summary, seedlings of the cultivar Claro were grown under controlled conditions as follows: 16/8 h day/night periods at 18 °C throughout the experiment.…”
Section: Culture Preparation and Seedling Infection Assaymentioning
confidence: 99%
“…Using greenhouse assays we tested whether isolates sampled from different time points or cultivars showed differences in virulence on the most frequent cultivar (CH Claro) planted in the field. For this, we analysed data generated for a genome-wide association study from a subset (n=120) of the isolates [45] (Table S5). We found that isolates from the third collection produced significantly more pycnidia (a proxy for pathogen reproduction) compared to earlier collection (one-way ANOVA, P=0.002) (Fig.…”
Section: Experimental Analyses Of Virulence On Cultivar Claromentioning
confidence: 99%
“…tritici (strain 3D7). The second fully unrolled leaf of 3-week-old plants were spray-infected with 10 ml of blastospores following a standard infection protocol (Singh et al, 2021). The inoculated plants were kept at 100% relative humidity and 21 0 C for 2 days, before going back to initial growth conditions (see above).…”
Section: Pathogen Assaymentioning
confidence: 99%
“…We tested using greenhouse assays whether isolates sampled from different time points or cultivars showed differences in virulence on the most frequent cultivar (CH Claro) planted in the field. For this, we analyzed data generated for a genome-wide association study from a subset (n = 120) of the isolates (Singh et al 2021, DOI pending; Supplementary Table S5). We found that isolates from the third collection to produce significantly more pycnidia (a proxy for pathogen reproduction) compared to earlier collection (one-way ANOVA, p-value = 0.002) (Figure 6A-B).…”
Section: Experimental Analyses Of Virulence On Cultivar Claromentioning
confidence: 99%
“…Z.tritici satisfies all these conditions, and a recent study has shown the successful application of GWAS to identify a candidate effector gene related to the pathogen's virulence (Plissonneau et al 2017;Singh, Badet, et al 2021;.…”
Section: General Introductionmentioning
confidence: 99%